Localized ridge augmentation using autogenous block bone graft followed by dental implant placement - K V Prabhakara Rao; Sasikala Pagadala (Wolters Kluwer Medknow Publications, 2012)
The placement of endosseous dental implants is often hampered by unfavourable anatomy of the alveolar bone. Most frequently patients lose their teeth due to alveolar bone loss, tooth extraction; trauma and long term use of removable appliances tend to lose the bone making it difficult for the placement of implant in an optimal prosthetic position. The loss of width of the residual alveolar ridge necessitated measures which could refurbish the lost dimensions. Here we report the successful management of such a condition wherein placement of implant was made possible by placement of autogenous bone block graft obtained from the mandibular symphysis region and predictable osseointegration thus achieved.